PERBANDINGAN KARAKTERISTIK KARBON AKTIF ARANG TEMPURUNG KELAPA DAN ARANG TEMPURUNG KEMIRI MENGGUNAKAN SCANNING ELECTRON MICROSCOPIC DAN FOURIER TRANSFORM INFRA RED - Lauri Leslie Mendame; Patricia Silangen; Alfrie Rampengan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Utilization of coconut shell and candlenut shell in Indonesia has not been used optimally as in North Sulawesi. The purpose of this research was to compare the characteristics of the pore size and functional groups of activated carbon, coconut shell charcoal and candlenut shell charcoal. The research method includes the activation stage and characterization of activated carbon using Scanning Electron Microscopic (SEM) and Fourier Transform Infra Red (FTIR). The results of this study are the characteristics of coconut shell charcoal activated carbon which has a larger pore size of 31.5 µm - 41.9 µm when compared to candlenut shell charcoal activated carbon which has a small pore size, namely 23.0 µm - 33.1 µm. . Both of these activated carbons have the same functional group, namely O-H, C=C, C-O, C-H which is an activated carbon composition.